Short Notice, Big Difference? The Effect of Temporary Employment on Firm Competitiveness across Sectors - Romina Giuliano; Stephan Kampelmann; Benoît Mahy; Francois Rycx (Institute of Labor Economics (IZA), 2017)
This paper is one of the first to examine how the use of fixed-term employment contracts (FTCs) affects firm competitiveness (i.e. productivity, wages and profits) while controlling for key econometric issues such as time-invariant unobserved workplace characteristics, endogeneity and state dependence. We apply dynamic panel data estimation techniques to detailed Belgian linked employer-employee data covering all years from 1999 to 2010. Results show that the effects of FTCs on firm competitiveness vary across sectors: while temporary employment is found to enhance productivity and profits in (labour-intensive) services, this is not the case in manufacturing and construction.
Keywords: D24; J24; J31; M12; 330; fixed-term contracts; productivity; wages; profits; sectors; linked panel data